2022
DOI: 10.1039/d2ce00830k
|View full text |Cite
|
Sign up to set email alerts
|

Low-cost synthesis of a nanocomposite of MoS2 and alkali-activated halloysite nanotubes for photocatalytic RhB degradation

Abstract: In this work, a novel nanocomposite of highly-dispersed MoS2 nanosheets supported on alkali-activated halloysite nanotubes (a-HNTs) was fabricated via a simple hydrothermal method. The alkali (5 M NaOH herein) could...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…8 Yet, its broader bandgap compared to TiO 2 makes ZnO less appealing for photocatalytic applications. [9][10][11][12] To circumvent this problem, researchers have doped ZnO with different metals such as Cr, Sm, Co, Cu, or Ag to improve the photocatalytic activity. 13,14 Among the promising dopants, Cu is preferred due to its advanced attributes such as low toxicity and abundance.…”
Section: Introductionmentioning
confidence: 99%
“…8 Yet, its broader bandgap compared to TiO 2 makes ZnO less appealing for photocatalytic applications. [9][10][11][12] To circumvent this problem, researchers have doped ZnO with different metals such as Cr, Sm, Co, Cu, or Ag to improve the photocatalytic activity. 13,14 Among the promising dopants, Cu is preferred due to its advanced attributes such as low toxicity and abundance.…”
Section: Introductionmentioning
confidence: 99%
“…27 This viewpoint is supported by the findings of Zeng et al, 28 who proposed that NaOH treatment can lead to the generation of hydroxyl groups on the surface of HNTs. Wang et al 29 suggested that NaOH can attack the inert outer surface of HNTs, resulting in abundant surface defects, thereby making the MoS 2 sheets uniformly distributed on the surfaces of HNTs. The as-prepared MoS 2 /a-HNT nanocomposite showed a significantly enhanced photocatalytic efficiency for the degradation of rhodamine B (RhB).…”
Section: Introductionmentioning
confidence: 99%